Pengaruh Senam Relaksasi Otot Progresif Terhadap Tekanan Darah Pada Lansia Dengan Hipertensi di Puskesmas Kayang - H. Pella, Yosin; M.B. Sappa, Siti; Roynaldo Pandie, Fance (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2024)
Hypertension is one of the killers of people because the majority of case do not show any symptoms and without realizing it, sufferers are already experiencing complications. The aim of this study was to analyze the effect of progressive muscle relaxation exercises on blood pressure in elderly people with hypertension at the Kayang Community HealthCenter, Pantar Barat Laut District, Alor Regency. Research method: Pre-experimental research type with pre test- post testone group only design. This research included all elderly people at the Kayang Community Health Center. With a population of eighty two, the sample taken was forty five respondents, using accidental sampling techniques, data collection using a digital blood pressure meter, and observation sheets, data processing using editing, coding, scoring tabulating and analysis using the McNemar statistical test with a=0.05. Results: Based on the results of research before being given progressive muscle relaxation exercises on blood pressure in elderly people with hypertension, thirty theree respondents were not hypertensive and twelve respondents were not hypertensive, after being given progressive muscle relaxation exercises, a small number of respondents were hypertensive, twelve respondents using statistical tests to obtain the ρ-value=0.000<0.05 then Hl is accepted Conclusion: There is an effect of progressive muscle relaxation exercises on blood pressure in the elderly at the Kayang health center. It is hoped that progressive muscle relaxation exercises will become one of the routine activities to control blood pressure in elderly people with hypertension.